Analysing protein-protein interface using JPIV. - YAMAGISHI, M. E. B. (2006)
Short Abstract: In this work we present Java Protein Interface Viewer (JPIV). It is a web-based software designed to visualize and analyse protein-protein interfaces. It uses Delaunay triangulation in order to define the interface, and the STING_DB physical-chemical parameters to the analysis process.